Analysis on Seepage Flow and Dam Stability of Ecological Permeable Dam. Issue 1 (January 2021) - Ma, Xiaotang; Jiang, Linlin; Zhao, Chuan
Abstract: In this paper, the Geo-studio finite element analysis software is used to establish a variety of dam models to analyze the seepage of permeable dam and the slope stability, the results of seepage data are compared by hydraulic physical model experiment. The results show that the single width seepage flow of the permeable dam is 0.0017398m 2 /s, which meets the design permeability; the XY rate of seepage of the dam meets the law of permeability coefficient mutation. The minimum safety factor is 1.0388, the most likely slip surface appears in the middle and lower part of the dam body facing the water surface, and the leakage point is above the reservoir in the dam, reinforce this area in advance to prevent seepage damage; the simulation process also showed that dams with similar permeability coefficients are safer and more reliable. These research results have certain reference value for the design and research of permeable dams in the future.